\(1,\\ a,=4x\left(x^2-2x+4\right)\\ b,=x\left(x-y\right)+8\left(x-y\right)=\left(x+8\right)\left(x-y\right)\\ c,=\left(x-y\right)\left(x+y\right)-6\left(x-y\right)=\left(x-y\right)\left(x+y-6\right)\\ 2,\\ a,\Leftrightarrow\left[{}\begin{matrix}4x+8=0\\x-5=0\end{matrix}\right.\Leftrightarrow\left[{}\begin{matrix}x=-2\\x=5\end{matrix}\right.\\ b,\Leftrightarrow\left(x-2\right)\left(6x-1\right)=0\Leftrightarrow\left[{}\begin{matrix}x=\dfrac{1}{6}\\x=2\end{matrix}\right.\\ c,\Leftrightarrow x\left(x-1\right)+7\left(x-1\right)=0\\ \Leftrightarrow\left(x+7\right)\left(x-1\right)=0\\ \Leftrightarrow\left[{}\begin{matrix}x=-7\\x=1\end{matrix}\right.\)